2019
DOI: 10.1371/journal.pntd.0007821
|View full text |Cite
|
Sign up to set email alerts
|

Erythritol as a single carbon source improves cultural isolation of Burkholderia pseudomallei from rice paddy soils

Abstract: BackgroundIsolation of the soil bacterium Burkholderia pseudomallei from tropical environments is important to generate a global risk map for man and animals to acquire the infectious disease melioidosis. There is increasing evidence, that the currently recommended soil culture protocol using threonine-basal salt solution with colistin (TBSS-C50) for enrichment of B. pseudomallei and Ashdown agar for subsequent subculture lacks sensitivity. We therefore investigated, if the otherwise rarely encountered erythri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 48 publications
1
21
1
Order By: Relevance
“…Using a defined medium also facilitates detection of microbial secreted products. Defined media designed for isolation often have a single substrate or nutrient source to select for specific organisms, which can be a complex substrate ( Davis et al, 2005 ; Trinh et al, 2019 ). Some defined media contain a synthetic carbon mixture based on soil extract or cell extracts ( Liebeke et al, 2009 ; Baran et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using a defined medium also facilitates detection of microbial secreted products. Defined media designed for isolation often have a single substrate or nutrient source to select for specific organisms, which can be a complex substrate ( Davis et al, 2005 ; Trinh et al, 2019 ). Some defined media contain a synthetic carbon mixture based on soil extract or cell extracts ( Liebeke et al, 2009 ; Baran et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A period of 48 h of incubation in Ashdown broth (Ashdown, 1979) were followed by a 96 h incubation in a minimal medium based on TBSS-C50 (Galimand and Dodin, 1982) with erythritol as a single carbon source. At this time, the erythritol-based medium was under development and differed from the version published later (Trinh et al, 2019) by the N source (0.1% ammonium chloride) and the addition of a diverse set of antibiotics (32 mg/L tobramycin, 50 mg/L colistin, 16 mg/L norfloxacin, 50 mg/L gentamicin, and 50 mg/L cycloheximide) (Goodyear et al, 2013). Enrichments were subcultured in serial dilutions on Ashdown agar.…”
Section: Soil Culture Methodsmentioning
confidence: 99%
“…Reliance on culture protocols to identify factors associated with the abundance of B. pseudomallei in the environment could be imprecise due to the low sensitivity of soil cultures. Previous studies have clearly shown that the current consensus methods for the culture (Limmathurotsakul et al, 2013) detection of B. pseudomallei lack sensitivity, leading to false-negative results (Trung et al, 2011;Gohler et al, 2017;Trinh et al, 2019). A study from Laos showed a higher detection rate of B. pseudomallei in enrichment cultures from soil samples by PCR when compared to B. pseudomallei growth in the respective subcultures (Dance et al, 2018), which is probably due to insufficient selectivity of the culture media used.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental B. pseudomallei strains were isolated as previously described ( 13 ). For bacterial DNA isolation, the strains were cultivated on Columbia agar supplemented with 5% sheep blood overnight.…”
Section: Methodsmentioning
confidence: 99%